KECEMASAN DAN MEKANISME PERTAHANAN EGO TOKOH UTAMA DALAM KUMPULAN CERPEN (LÇ” XÃ¹n XiÇŽoshuÅ QuÃ¡njÃ é²è¿…å°è¯´å…¨é›†) KARYA LU XUN (Kajian Psikoanalisis Sigmund Freud) - Dwi Didik Santoso (Paramasastra : Jurnal Ilmiah Bahasa Sastra dan Pembelajarannya, 2017)
This research aims to study psychoanalysis main character in the short story collection Lu Xun entitled (LÇ” Xun XiÇŽoshuÅ QuÃ¡njÃ é²è¿… å°è¯´ å…¨é›†) Works of Lu Xun which include (1) concerns the main character (realistic anxiety, neurotic anxiety, and moral anxiety), (2) the cause the main character of anxiety (realistic anxiety, neurotic anxiety and moral anxiety), (3) the main character's ego defense mechanisms (repression, sublimation, projection, transfer, rationalization, regression, identification, denial of reality, intellectualization, redemption. Datas of this study focuses on anxiety and ego defense mechanism in the collection of short stories (LÇ” Xun XiÇŽoshuÅ QuÃ¡njÃ é²è¿… å°è¯´ å…¨é›†) Works of Lu Xun. The researcher uses descriptive analysis techniques. Descriptive analysis techniques are done by describing the facts which are then followed by analysis. The total of 153 data was collected data; anxiety realistic citations, 34; neurotic anxiety; 56, anxiety morals; 5, repression; 31, intellectualization; 4, denial of reality; 2, identifying; 6, redemption; 1, reaction formation; 5, the projection; 2, and rationalization ,7 respectively. In consideration of the research result, (1) neurotic anxiety dominates so the purpose (2) also dominated, for the purpose of (3) ego defense mechanism of repression dominate.